TAʿLĪM AL-LUGAH AL-ʿARABIYYAH LADA AL-TALĀMĪḎ MIN UṢŪL AL-ʿARAB - Nurul Aina (UIN ANTASARI, 2020)
Students of Arab origins are children who first know the Arabic language from their families before learning in school. Therefore, their discourse when teaching Arabic is definitely better than other students who are not of Arab descent. The specificity of the discourse language of Arab individuals certainly affects their children in discourse. This is seen in acoustic signs in the speech. The reason is that the phonology of every language in the world has its own characteristics. We can see the characteristics of phonology in language from a variety of phonology in Arabic and other languages.Therefore, the researcher “Teaching Arabic to Student of Arab origins at Anak Sholeh Mandiri Primary School in Banjarmasin (audio study with the Software Praat ).To learn how to teach Arabic language and the characteristics of Students of Arab origins in the Islamic Primary School Anak Sholeh Mandiri in terms of phonetics. The researcher analyzes descriptive kualitatif and the software Praat ready program because it is one of the well-known ready-made program in Amsterdam and the best sound meter tools because it analyzes accurately and completely.The results of this research are:Teaching the Arabic language to Students of Arab origins at the Anak Sholeh Mandiri Islamic Primary School in Banjarmasin is organized into three departments, namely planning, implementation and evaluation. The planning of teaching the Arabic language to students of Arab origins in the Anak Sholeh Mandiri Islamic Elementary School in Banjarmasin is excellent, which consists of: education objectives, teaching materials, teaching activities, teaching methods, their sources and evaluation. And its implementation is very good, because its implementation is appropriate in most of the educational activities that are organized in stages to achieve the educational goals, and stages consisting of opening activities, basic activities and closing activities. As for evaluating it with an excellent degree, because it is evaluated by planning and organizing before the activities, that an evaluation is held four times in the middle, and the evaluation is made appropriate to all skills and is appropriate to the objectives of education and teaching materials. The exercises are varied.And the phonological characteristics of Arab students of Anak Sholeh Mandiri Primary School in Banjarmasin, analyzed by